Government land leasing and intersections with housing in the Northwest Territories - Van Dyke, Chris (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
With increasing attention cast on the use of public land for housing, the Northwest Territories (NWT) offers a relevant case study. ‘Public’ land in the territory has been a site for homes for decades, particularly in its smaller communities, where thirty percent of homeowner households sits on a government land lease. This article explores this unique practice and situates it within the broader conversation on the intersection between land and housing. Using a mixed-methods approach combining data and correlation analysis with content analysis of territorial Hansard records, I contextualize NWT land policy and find significant differentiation in the prevalence of residential land leases, including by region and community size. Further, I show that the approach to leasing land for housing in the NWT serves as a barrier to improving housing outcomes in the territory, particularly in predominantly Indigenous communities outside the regional administrative centres, including in regions where modern treaties exist. I conclude by calling for a more nuanced approach to land policy in the NWT that centres Indigenous communities and recognizes the role such policy plays in informing housing outcomes.